(untitled) (Revista Brasileira de Pesquisa em Educação em Ciências, 2023)
From the interpretive perspective of the concept of culture (Geertz) and the different postcolonial developments of cultural analysis (Bhabha; Hall; Garcia-Canclini), put in dialogue with the concept of the arts of doing (Certeau), discussions and a critical review of the scope, limitations and challenges of the cultural approach to the understanding and construction of science teaching processes in the urban peripheries of Latin America are generated. With this panorama, the concept of Anthropophagic Interculturality is projected as a dynamic that in the framework of Epistemologies of the South, would complement the notion of Intercultural Translation allowing the judicious and critical appropriation of scientific knowledge, while at the same time valuing other knowledge, communal, ancestral, hybrid and popular, putting them in contact and/or dialogue based on the desires and needs of the oppressed populations of the Global South.